Letter to editor Eye Camp Surgery: Doi. 10.36351/pjo.v38i1.1329 - Jamil, Ahmad Zeeshan; Bahoo, Muhammad Luqman Ali (Pakistan Journal of Ophthalmology, 2021)
Cataract surgery is the most frequently performed operative procedure in the human body.1 In Pakistan, we have very meagre trained Human Resources and equipment.2 At onetime, eye-camp surgery was promoted by the government to tackle the growing burden of cataract-related blindness. As time passed on, we developed public and private health care delivery services. Now we have ample resources to deal with an ever-growing number of cataracts. In the current scenario, eye camp surgery is not justified. But it seems as if government and regulatory bodies have no intentions to focus on this point.